2023
DOI: 10.1182/bloodadvances.2022007254
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic myeloid-derived suppressor cells to prevent and treat murine immune-mediated bone marrow failure

Abstract: Myeloid-derived suppressor cells (MDSCs) are immature myeloid cells which originate in the bone marrow (BM) and have immunoregulatory functions. MDSCs have been implicated in the pathogenesis of several autoimmune diseases but have not been investigated in immune aplastic anemia (AA). We examined the roles of granulocytic-MDSCs (G-MDSCs) in murine models of human AA and bone marrow failure (BMF). As both prophylaxis and therapy, BM-derived G-MDSCs improved pancytopenia and BM cellularity and suppressed BM T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…We estimated, based upon published frequencies of these cells in the BM and spleen of mice [48,49,53], that these myeloid cells may approximate or exceed the numbers of allogeneic T cells within the BM and spleen. Feng et al have recently reported that PMN-MDSCs potently suppress T cell-mediated BM failure using a mouse model of immune-mediated aplastic anemia [82]. Conceptionally, these data are similar to those of Dong et al who reported that patients with severe immune-mediated aplastic anemia have fewer circulating M-MDSCs that possess impaired immunosuppressive activity [83].…”
Section: Potential Mechanism Involved In Suppressing Disease In Outbr...supporting
confidence: 73%
“…We estimated, based upon published frequencies of these cells in the BM and spleen of mice [48,49,53], that these myeloid cells may approximate or exceed the numbers of allogeneic T cells within the BM and spleen. Feng et al have recently reported that PMN-MDSCs potently suppress T cell-mediated BM failure using a mouse model of immune-mediated aplastic anemia [82]. Conceptionally, these data are similar to those of Dong et al who reported that patients with severe immune-mediated aplastic anemia have fewer circulating M-MDSCs that possess impaired immunosuppressive activity [83].…”
Section: Potential Mechanism Involved In Suppressing Disease In Outbr...supporting
confidence: 73%
“…The thymus and lymph nodes were collected from donor C57BL/6J mice, homogenized, centrifuged, and resuspended to obtain the lymphocyte suspension by combining thymocytes and lymph node cells at a ratio of 1:2. Except for the control group, all other groups were established by the total body X-ray radiation, followed by intravenous injection of 0.2 mL of the lymphocyte suspension [ 26 ]. Drug administration started 24 h after modeling.…”
Section: Methodsmentioning
confidence: 99%
“…new cell therapy and found that G-MDSC therapy is effective in the treatment of murine AA in the minor-H mismatched LN-cell-infusion-induced BMF model [12].…”
Section: G-mdsc-exos Confirmation and Quantificationmentioning
confidence: 99%
“…We used these models to test granulocytic myeloid-derived suppressor cells (G-MDSCs) as a new cell therapy and found that G-MDSC therapy is effective in the treatment of murine AA in the minor-H mismatched LN-cell-infusion-induced BMF model [12].…”
Section: Introductionmentioning
confidence: 99%